2013
DOI: 10.1007/s11434-012-5463-x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling cavitation flow of cryogenic fluids with thermodynamic phase-change theory

Abstract: Cavitation is the formation of vapor bubbles within a liquid where the flow dynamics causes the local static pressure to drop below the vapor pressure. The so-called full cavitation model (FCM) developed by Singhal has been widely used in numerical modeling of the cavitation flow for thermosensible and non-thermosensible fluids. Within the FCM, the bubble size is taken to be equivalent to the maximum possible value to forego the calculation of bubble number density. We developed a new cavitation model by re-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Combing the two equations finally leads to the following expressions relating the local pressure and the bubble radius. Details regarding the details of the derivation can be found elsewhere [25,26].…”
Section: Kunz Et Al (2000) [18]mentioning
confidence: 99%
“…Combing the two equations finally leads to the following expressions relating the local pressure and the bubble radius. Details regarding the details of the derivation can be found elsewhere [25,26].…”
Section: Kunz Et Al (2000) [18]mentioning
confidence: 99%
“…Thus, numerous studies have been conducted to predict cavitating flows accurately by focusing on various research objects such as Francis turbines [7], hydrofoils [8], centrifugal pumps [9,10], cryogenic fluids [11], marine propellers [12,13], and waterjet propulsors [14][15][16][17]. Rhee et al [18] found that cavitation inception and cavity shape in a marine propeller could be predicted well using an unstructured grid, which demonstrated the feasibility of cavitation simulation based on Reynoldsaveraged Navier-Stokes (RANS) method.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation of cavitating flows is a challenging problem as it is quite complicated, involving fully developed turbulent flow [9][10][11][12]. The interaction between cavitation and turbulence is not completely understood yet.…”
Section: Introductionmentioning
confidence: 99%